Berseem Clover (Trifolium Alexandrinum L.) Seed Yield and Seed Quality Response to Irrigation Frequency and Foliar Spray of Plant Bio-Regulators (SAARC Journal of Agriculture, 2023)
The primary challenges in Berseem clover (Trifolium alexandrinum L.) seed production in Nepal are low productivity levels and substandard quality indicators. To address this issue, the experiments were conducted at the Regional Agricultural Research Station, Khajura, Banke, Nepal, and replicated in farmers' fields using a Randomized Complete Block Design from November 2018 to June 2019. Four irrigation schemes and three levels of foliar sprays of plant bio-regulators were used. The experiment result revealed that three and four irrigations were most suitable for achieving higher seed yield (p